Learning how to learn: eight lessons for impact evaluations that make a difference - and Ramalingam, Ben (ODI, 2011)
This Background Note outlines key lessons on impact evaluations, utilisation-focused evaluations and evidence-based policy. While methodological pluralism is the key to effective impact evaluation in development, the focus here is on the factors that need to be considered for impact evaluations to be used in policy and practice – regardless of the method employed.